Direct Organocatalytic Enantioselective Functionalization of SiOx Surfaces. (29th June 2018) - Parkin, John D.; Chisholm, Ross; Frost, Aileen B.; Bailey, Richard G.; Smith, Andrew D.; Hähner, Georg
Abstract: Traditional methods to prepare chiral surfaces involve either the adsorption of a chiral molecule onto an achiral surface, or adsorption of a species that forms a chiral template creating lattices with long range order. To date only limited alternative strategies to prepare chiral surfaces have been studied. In this manuscript a "bottom‐up" approach is developed that allows the preparation of chiral surfaces by direct enantioselective organocatalytic reactions on a functionalized silicon oxide supported self‐assembled monolayer (SAM). The efficient catalytic generation of enantiomerically enriched organic surfaces is achieved using a commercially available homogeneous isothiourea catalyst that promotes an enantioselective Michael‐lactonization process upon a silicon‐oxide supported SAM functionalized with a reactive trifluoroenone group. Chiral atomic force microscopy (χ‐AFM) is used to probe the enantiomeric enrichment of the organic films by measurement of the force distributions arising from interaction ofd ‐ orl ‐cysteine‐modified AFM tips and the organic films.